EFFECT OF ALKALI TREATMENT ON MECHANICAL AND THERMAL PROPERTIES OF SISAL FIBER FOR COMPOSITE APPLICATIONS - Parahdiba, Nursyahbani Putri; Anam, Khairul; Gapsari, Femiana; He, Rui-En (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2026)
The demand for sustainable and high-performance composite materials has driven extensive research on natural fiber reinforcements, including sisal fiber, to enhance their mechanical and thermal properties. However, the inherent hydrophilicity and weak interfacial adhesion of sisal fibers limit their effectiveness in composite applications. In this study, untreated and alkali-treated sisal fibers were characterized using tensile testing, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). The results showed that alkali treatment reduced tensile strength from 2080 MPa to 1142.1 MPa but slightly increased elongation at break from 2.5% to 2.9%, while XRD analysis indicated a higher crystallinity index, and TGA confirmed improved thermal stability with an increased decomposition temperature from 220°C to 260°C. These findings provide valuable insights into optimizing sisal fiber treatment for enhanced fiber-matrix interactions, contributing to the development of more durable and sustainable natural fiber composites.